A case study on the circulation spaces inside a selected mall in Pasig City in terms of accessibility and mobility of older persons - Cresencio, Ma. Hannah R.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The study utilized a single case study approach in an attempt to evaluate whether the interior design of circulation spaces inside a newly constructed mall in Pasig City addressed the accessibility and mobility needs of older persons. Through snowball sampling technique, fifteen 15 respondents were chosen to take part in the interviews about their experiences inside Mall X. Data gathering procedures for this study included: 1 ocular observation of the mall based from Batas Pambansa 344, and 2 interviews. Instrumentation for this study included: 1 an observation guide, 2 camera for photo documentation, 3 drafting tools to come up with the floor plans of the four mall levels, 4 an interview guide, and 5 a cell phone for recording the interviews. Analysis of data was grounded on Universal Design. Findings show that Mall X is compliant with most of the requirements from Batas Pambansa 344, especially in terms of signages, and dimensions of circulation spaces. Wayfinding, layout of the mall, and the people mall personnel and companions promoted the accessibility and mobility of older persons. However, as far as comfort is concerned, the mall may not have taken this much into consideration. To address these concerns and further improve the accessibility and mobility of older persons inside Mall X, the researcher recommends the following inside Mall X: 1 additional and equal distribution of seat furniture, 2 additional information boards and maps, and 3 slip-resistant flooring in areas most accessed by the public. The researcher believes that people from different sectors and professions must come hand in hand in providing accessible and safe environments for older persons. These pave way for them to enjoy their rights and privileges provided by the laws in the Philippines.
submitted May 2018
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Barrier-free design for older people -- Philippines -- Pasig City; Shopping malls -- Philippines -- Pasig City -- Barrier free design